The effects of recombinant human insulin-like growth factor I on growth hormone secretion in adolescents with insulin dependent diabetes mellitus. - Cheetham, T; Clayton, K; Taylor, A; Holly, J; Matthews, DR; Dunger, D (1994)
OBJECTIVE: It has been proposed that low IGF-I levels and reduced IGF-I bioactivity may lead to elevated GH levels in adolescents with insulin dependent diabetes (IDDM). We have therefore studied the effects of human recombinant insulin-like growth factor I (rhIGF-I) administration on GH levels and GH secretion in adolescents with IDDM. PATIENTS: Nine late pubertal adolescents (four male and five female) with IDDM. DESIGN: A double-blind placebo controlled study of rhIGF-I administered subcutaneously in a dose of 40 micrograms/kg body weight at 1800 h. MEASUREMENTS: IGF-I and GH concentrations were measured at regular intervals throughout the study. Twenty-two hour GH secretory rates were calculated by deconvolution analysis. Overnight GH profiles were analysed by distribution analysis, and Fourier transformations were performed on both overnight GH concentrations and GH secretory rates. RESULTS: Mean IGF-I levels over the 22-hour study period were significantly elevated following rhIGF-I administration (350 +/- 26 vs 205 +/- 21 micrograms/l (mean +/- SEM), P < 0.01). Mean 22-hour GH levels were reduced following rhIGF-I administration (19.4 +/- 4.0 compared with 33.6 +/- 5.8 mU/l; P = 0.01). Distribution analysis demonstrated that the reduction in GH levels was due to changes in the proportion of values at both high and low concentrations. Deconvolution analysis also revealed a significant overall reduction in GH secretory rate following IGF-I administration (1.81 +/- 0.30 vs 2.98 +/- 0.47 mU/min, P = 0.01) which was still apparent during the final 5.5 hours of the study period (1.51 +/- 0.30 vs 2.76 +/- 0.61 mU/min, P = 0.02). The dominant periodicity of GH secretory episodes as determined by Fourier transformation was between 120 and 180 minutes after both IGF-I and placebo. CONCLUSIONS: In late pubertal adolescents with IDDM the rise in IGF-I levels following rhIGF-I administration in a subcutaneous dose of 40 micrograms/kg body weight leads to a significant reduction in GH levels and GH secretory rate. The reduction in GH secretion is due to changes in pulse amplitude rather than frequency. A reduction in GH secretion was apparent at the beginning and also towards the end of the 22-hour study period.